Kontribusi Program Full Day School Terhadap Peningkatan Motivasi Belajar Siswa Di Sekolah Dasar - Septiani, Liza; Movitaria, Mega Adyna; Usman, Usman; Arif, Mahmud (Institut Agama Islam Sumatera Barat Pariaman, 2025)
This study was driven by observations that revealed several issues: students showed low enthusiasm for learning due to long study hours, some left and re-entered the classroom out of boredom, and others became sleepy during lessons because they were tired and struggled to concentrate. The purpose of this study was to assess the contribution of the full day program to students’ learning motivation at SD Negeri 01 Pauh Kurai Taji. A quantitative method with an experimental approach was used. The study population consisted of all 323 students at SD Negeri 01 Pauh Kurai Taji, with a sample of 39 students. Data were collected using a questionnaire. The data analysis included normality tests, homogeneity tests, and hypothesis tests. The study’s results indicated that the full day program had a positive contribution to students’ learning motivation. This conclusion was based on the results of the T-Test, where the significance value was 19.238 > 0.05 and the t count was 19.238 < t table 2.024. This means H0 was accepted and Ha was rejected, indicating that the full day school program contributed to improving students’ motivation to learn. The additional school hours allowed for more activities that helped increase student motivation.